وسائل الاستثمار للحسابات الاسنثمارية لدى المصارف الإسلامية : دراسة نقدية فقهية - Muhammad Awal Gali
This study aims at highlighting the importance of the Islamic Banking Systems of investment and the judicious distribution of its profits to the investors who deposit their money in investment accounts with these Banks.The researcher depends,in his research, on the deductive and analytical approaches in order to acquire the desired results. The study has found out that the investors deposit their money to the Banks for investment due to the Shari'ah various means of investment that attract the desired profits;that the Bank distributes the profits earned through these means to the depositor based on the agreed terms by the parties to the contact; and that the Islamic bank came-up to meet the wishes of the Muslim communities in finding channel to handling bank dealings, away from the use of interest rates and usury. The study therefore sheds more light on the establishment of Islamic banks and the objectives for which they are established; on the roles the played in the Muslim community and the explanation of what these bank do for the investment of funds deposited with them in accordance with the laid down guidelines by Shari'ah. It shows the means by which the Islamic banks deal with investment and funding with the money placed in the investment accounts; such as contract of partnership, like Al-Mudarabah (profit sharing contract) and Al-Musharakah (profit and loss sharing contract); the investment by Agency contracts; Tawarruq Contract (purchasing an asset with deferred price, either on the basis of musawamah or murabahah then, selling it to a third party to obtain cash); Murabaha (sale contract with a disclosure of the assets cost price and profit margin to the buyer); Ijara (lease contract); Salam etc, in accordance to what has become common practice in Islamic law of contract and, for the purpose of waging war against the forbidden usury. Finally, the study exposes the risk in distorted sale contract and transactions that are based on usurious bank interest . It discusses the opinions of contemporary jurist and their way of deducting Shari'ah legal provisions that are applicable to Islamic financial institutions. It also touches the methods adopted by these banks on the distribution of the profits to the owners of these investment accounts.